RNA-seq Profiling Showed Divergent Carbohydrate-Active Enzymes (CAZymes) Expression Patterns in Lentinula edodes at Brown Film Formation Stage Under Blue Light Induction - Huang, Xiying; Zhang, Runji; Qiu, Yijie; Wu, Haibing; Xiang, Quanju; Yu, Xiumei; Zhao, Ke; Zhang, Xiaoping; Chen, Qiang; Penttinen, Petri; Gu, Yunfu (Frontiers in Microbiology, 2020)
Lentinula edodes (shiitake mushroom) is one of the most important edible mushrooms worldwide. The L. edodes cultivation cycle includes a unique developing stage called brown film formation that directly affects the development of primordium and the quality of fruiting body. Brown film formation is induced by light, especially blue light. To promote our understanding of the role of blue light in brown film formation mechanisms of L. edodes, we used RNA-seq and compared the transcriptomes of L. edodes grown under blue light and in dark, and validated the expression profiles using qRT-PCR. Blue light stimulated the formation of brown film and increased the content of polysaccharides in L. edodes. Blue light also promoted L. edodes to absorb more polysaccharides by enhancing the activities of enzymes. Among the 730 differentially expressed genes (DEGs), 433 genes were up-regulated and 297 were down-regulated. Most of the DEGs were in the oxidoreductase activity group. Pentose and glucuronic acid conversion and starch and sucrose metabolism were the most important pathways in the formation of brown film. A total of 79 genes of DEGs were identified as genes encoding carbohydrate-active enzymes (CAZymes). 51 of the CAZymes genes were up-regulated, suggesting that CAZymes play important roles in brown film formation to provide sufficient nutrition for L. edodes. The results will facilitate future functional investigations of the genes involved in the developmental control of L. edodes.